Measurement invariance of the driving inattention scale (ARDES) across 7 countries - Castro, Candida (2024)
Th e Atte ntion -Relate d Dr iving Errors Scal e (ARDES ) is a self-report me asure of indivi dua l di ffe rence s in dr iving inatte ntion . ARDE S wa s orig inall y deve loped in Spanis h (A rgentina) , an d late r adapte d to othe r countrie s an d la nguages . Ev idenc e su pportin g th e reli abi lit y an d vali dit y of ARDE S scores ha s been obtained in va r iou s di ffe r - en t countries. Ho wever , no stud y ha s been co nducted to specificall y examin e th e me asurement invariance of ARDE S me asure s across countries, thus li mitin g thei r co mparabi lity. Ca n di ffe ren t la nguag e ve rsion s of ARDE S pr ovide co mparabl e me asure s across countrie s with di ffe ren t traffi c re g ulation s an d cu ltura l norms? To what ex - tent migh t cu ltura l di ffe rence s pr event researcher s from ma kin g vali d infe rence s base d on ARDE S me asures? Us - in g Alig nment Anal ysis, th e pr esent stud y assessed th e approx imate invariance of ARDE S me asure s in seve n countries: Argentin a ( n = 603) , Au stralia ( n = 378) , Brazil ( n = 220) , Chin a ( n = 308) . Spai n ( n = 310) , UK ( n = 298) , an d US A ( n = 278) . Th e thre e -factor stru cture of ARDE S scores (diffe rentiatin g dr iving errors occu r - ring at Na v igation , Manoeuvrin g an d Co ntrol le vels) wa s used as th e ta rge t th e ore t ica l model. A fixe d alig nment anal ysi s wa s co nducted to examin e approx imate me asurement invariance . 12.3 % of th e inte rcept s an d 0. 8 % of th e item -factor loadings were identified as no n -invariant, averagin g 8. 6 % of no n -invariance . Despit e su bstantial di ffe rence s amon g th e countries, sa mpl e recrui tment or re prese ntativeness, stud y result s su pport resortin g to ARDE S me asure s to make co mpa rison s across th e countr y sa mples . Thus , th e rang e of cu ltures, laws an d co llision risk across thes e 7 countrie s pr ovide s a demandin g assessment fo r a cu ltura l -free inatte ntion whil e -driving. Th e alig nment anal ysi s result s su ggest that ARDE S me asure s reac h near equi v alenc e amon g th e countrie s in th e study. We hope this stud y will serv e as a basi s fo r future cros s -cultural research on dr iving inatte ntion usin g ARDES.